2023
DOI: 10.3389/fendo.2023.1218442
|View full text |Cite
|
Sign up to set email alerts
|

Retinal vein changes in patients with high-risk proliferative diabetic retinopathy treated with conbercept and panretinal photocoagulation co-therapy: a cohort study

Mingwei Si,
Yuan Tao,
Ziniu Zhang
et al.

Abstract: ObjectiveThis study aimed to observe and compare retinal vein diameter changes and other essential indicators in patients with high-risk proliferative diabetic retinopathy (PDR) treated with intravitreal injection of conbercept (IVC) combined with panretinal photocoagulation (PRP) versus PRP monotherapy.MethodsA retrospective analysis was conducted on data from patients with high-risk PDR who received specific treatment and were followed up for 24 months. Among 82 patients with high-risk PDR, 50 eyes received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The long-term follow-up studies used more than one or two intravitreal injections in cases without NV regression or in cases of NV relapse throughout the study. In all these studies, a necessity for the continuation of intravitreal treatment after the application of initial doses was indicated [ 41 , 42 , 43 , 45 , 46 , 47 , 48 ]. These findings indicate that total regression of NV cannot be obtained with only a small number of anti-VEGF injections.…”
Section: Summary Of the Results And Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The long-term follow-up studies used more than one or two intravitreal injections in cases without NV regression or in cases of NV relapse throughout the study. In all these studies, a necessity for the continuation of intravitreal treatment after the application of initial doses was indicated [ 41 , 42 , 43 , 45 , 46 , 47 , 48 ]. These findings indicate that total regression of NV cannot be obtained with only a small number of anti-VEGF injections.…”
Section: Summary Of the Results And Discussionmentioning
confidence: 99%
“…One study reported improvements in the condition of the ellipsoid zone and external limiting membrane among the PRP plus IVR and IVR monotherapy groups [ 43 ]. The recent study by Si et al [ 48 ] evaluated changes in angio-OCT vascular parameters after PRP plus and PRP treatments. The foveal avascular zone area and number of microaneurysms decreased more, and the vessel density of the superficial capillary plexus significantly increased in the combination group.…”
Section: Summary Of the Results And Discussionmentioning
confidence: 99%
See 1 more Smart Citation